1996
DOI: 10.1074/jbc.271.42.26267
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of NFκB Activity through Maintenance of IκBα Levels Contributes to Dihydrotestosterone-mediated Repression of the Interleukin-6 Promoter

Abstract: Androgens repress expression of many genes, yet the mechanism of this activity has remained elusive. The cytokine, interleukin-6, is active in a variety of biological systems, and its expression is repressed by androgens. Accordingly we dissected the mechanism of androgen's ability to inhibit interleukin-6 expression at the molecular level. In a series of co-transfection assays, we found that 5␣-dihydrotestosterone, through the androgen receptor, repressed activation of the interleukin-6 promoter, in part, by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
78
1
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(88 citation statements)
references
References 76 publications
8
78
1
1
Order By: Relevance
“…Aging is associated with an increased activation of NFkB in different tissues [34][35][36] and an increased secretion of proinflammatory cytokines. 7,8 As both parameters represent critical cellular responses to TLR and NLR activation, we further assessed these signaling events in our samples.…”
Section: Discussionmentioning
confidence: 99%
“…Aging is associated with an increased activation of NFkB in different tissues [34][35][36] and an increased secretion of proinflammatory cytokines. 7,8 As both parameters represent critical cellular responses to TLR and NLR activation, we further assessed these signaling events in our samples.…”
Section: Discussionmentioning
confidence: 99%
“…42,56,57 Conversely, AR and NFjB counteract in transcription assays. 58 Indeed, reporter assays showed high basal NFjB activity in PC-3 cells, which was decreased upon transient transfection with AR WT and diminished further by DHT (Fig. 5a, left).…”
Section: Ar Activation Lowered Nfjb Levels and Activitymentioning
confidence: 99%
“…Normal prostate cells are highly resistant to death receptor-induced cell apoptosis due to activation of NF-κB, which promotes cell proliferation and inhibits apoptosis (93). It has been reported that androgens inhibit TNF-α-induced NF-κB activation via multiple mechanisms (94)(95)(96) (Fig. 2.2).…”
Section: Androgen Action On Prostate Cell Apoptosis/ Survivalmentioning
confidence: 99%
“…2.2). Keller et al showed that androgens prevent the degradation of IκBα, which binds to NF-κB and inhibits its activation (95). AR activation also results in a decrease in RelA/p65, a subunit of NF-κB, thereby reducing its nuclear localization and transcriptional activity (97).…”
Section: Androgen Action On Prostate Cell Apoptosis/ Survivalmentioning
confidence: 99%